Abdominal wall endometriosis: An 11-year retrospective observational cohort study. (October 2019) - Marras, Sandra; Pluchino, Nicola; Petignat, Patrick; Wenger, Jean-Marie; Ris, Frédéric; Buchs, Nicolas C.; Dubuisson, Jean
Abstract: Objective: The objective of this study was to review the records of patients with excised abdominal wall endometriosis (AWE) to determine patient characteristics, diagnostic methods, presence of concurrent pelvic endometriosis and type of surgery. Study design: Medical records from an 11-year period were searched to identify histologically confirmed AWE cases. Descriptive data were collected and analyzed. Two subgroups were differentiated: isolated AWE and pelvic endometriosis-associated AWE. Results: Thirty-five women with AWE were included. The most common symptom was cyclic abdominal or parietal pain (68.6%); 17.1% of the women had no symptoms. Twenty-nine women (82.8%) had a history of gynecological or obstetrical surgery, most commonly cesarean section (CS). The mean interval between prior surgery and appearance of symptoms was 5.3 years. Six women (17.1%) had no prior surgery; all six presented with umbilical nodules, nulliparity and confirmed mild to severe pelvic endometriosis. Among all patients, 34.3% had concurrent pelvic endometriosis, 40% presented with isolated AWE and 25.7% had no pelvic exploration. Women with concurrent pelvic endometriosis had significantly lower parity, smaller nodule size and a higher likelihood of umbilical location than those with isolated AWE (p < 0.05). A history of CS was more commonly found in women with isolated AWE. The overall recurrence rate over the study period was 11.4%, with a mean follow-up period of 5.2 years. Conclusions: AWE is an uncommon condition associated with long diagnostic and therapeutic delays. In patients with umbilical AWE and no surgical history, pelvic endometriosis is commonly present and should be highly suspected.